Exploring Biochar Briquettes from Biomass Waste for Sustainable Energy - Andhina Putri Heriyanti; Sitty Nur Syafa Bakri; Abdul Jabbar; Putri Alifa Kholil; Rizki Nor Amelia; Erna Noor Savitri; Rifaatunnisa; Siti Herlina Dewi; Habil Sultan (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
The increasing demand for renewable energy necessitates sustainable alternatives such as biochar briquettes derived from agricultural waste. This study aims to optimize the production process and evaluate the physical, mechanical, and combustion properties of biochar briquettes made from corn residues, rice husks, and coconut shells. The methodology includes biomass carbonization, binder ratio optimization, and systematic testing of key quality parameters such as moisture content, density, ash content, and calorific value. Results indicate that an optimal biomass-to-binder ratio yields a high calorific value (7,192 kcal/kg) and low ash content (3.57%), enhancing combustion efficiency. Maintaining moisture content below 10% enhances ignition and prolongs burning time. These findings highlight biochar briquettes' role in carbon sequestration, biomass conversion, and sustainable waste management, supporting the circular economy and reducing environmental pollution. Biochar briquettes offer a clean, accessible energy solution, contributing to global energy security and climate change mitigation.